TANTANGAN MADRASAH SEBAGAI INSTITUSI PENDIDIKAN ISLAM - Mildawati, Titi; Usman, Syahruddin; Usman, Syarifuddin (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
The era of globalization brings various challenges that need to be overcome by Islamic educational institutions in order to remain relevant and effective in providing education to students, including madrasas as Islamic educational institutions that must compete in the digital era. These challenges include adaptation to information and communication technology (ICT) as well as the use of digital platforms to support the learning process and management of madrasas. The aim of this research is to find out the main challenges faced by madrassas as Islamic educational institutions, namely the increasing influence of foreign culture, technology and social media. developing, changes in curriculum and learning methods. Based on the discussion above, the author concludes that there are two types of challenges for madrasas as Islamic educational institutions or institutions, namely challenges from within such as madrasa management and challenges from outside the institution itself such as technological developments that are oriented towards foreign culture